A perspective approach to sustainable routes for non-isocyanate polyurethanes. (February 2017) - Cornille, Adrien; Auvergne, Rémi; Figovsky, Oleg; Boutevin, Bernard; Caillol, Sylvain
Graphical abstract: Abstract: Sustainable routes for the synthesis of polyurethanes with industrial applications are discussed in this article. Polyurethane is currently one of the most commonly used polymers worldwide for various applications such as rigid and flexible foams, coatings, elastomers, adhesives and sealants. However, isocyanate precursors are very harmful at each stages of the life cycle of the polymers. Hence, new synthesis routes for isocyanate-free polyurethanes are reported in literature, but most of them suffer from significant lacks that prevent any industrial application. This feature article focuses on the new challenges and new opportunities of these routes. A first part is dedicated to the market, the manufacture and the hazards of polyurethanes. In a second part, this article deals with the synthesis routes leading to non-isocyanate polyurethane. Hence, the advantages and limits of these routes are reported and discussed. Finally the outlooks for a future and industrial use of non-isocyanate polyurethane in industry are examined.